ALBUMIN AND ITS ROLE IN UROLITHIASIS - Raizada, Devesh; Kumar, Pragya; Singh, Tanya; Pruthi, Trisha; PRIYADARSHINI (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Urolithiasis is a multifactorial disease with an incidence rate of more than one million cases reported annually in India. Various forms of the calculus have been reported to have 90-95% inorganic and 5% organic matter. Out of the major proteins that comprise this organic component of the matrix, albumin, and uromodulin are found to be the most abundant. Albumin is also the most abundant protein in the human blood serum where it plays the role of a transporter of hormones, fatty acids, and other compounds. The increased concentrations of albumin may significantly affect a patient's susceptibility to kidney stone formation. The study of the role of albumin in urolithiasis could give us useful insights on its potential role in this disease and may add to the therapeutic repertoire of albumin.